The Relationship Of Javanese Culture And belief in Care Of Perineal Wounds in Post partum Mothers at pratama nabila Clinik year 2021 - Lisdayanti Simanjuntak (Institute of Computer Science (IOCS), 2021)
Perineal wounds are perineal injuries to the urogenital diaphragm and laterol ani muscles, postpartum period after delivery is complete up to 6 weeks or 42 days. Care for perineal wounds must be paid close attention because the 60% maternal mortality rate occurs during the puerperium. The relationship between culture and health is very closely related. Trust is a belief in one of the psychological states when someone considers a rationale or reason to be correct. Purpose To find out whether there is a relationship between Javanese Culture and Belief in Perineal Wound Care in Post Partum Mothers. The research design is analytic with a cross-sectional design, in this study the researcher made observations or measured variables at one particular moment. Research Methods The author's research collected data through primary secondary data by conducting interviews with the research instrument in the form of a questionnaire.